Cardiorespiratory and metabolic characteristics of detraining in humans - Mujika, I.; Padilla, S. (Medicine & Science in Sports & Exercise, 2001)
Detraining can be defined as the partial or complete loss of training-induced adaptations, in response to an insufficient training stimulus. Detraining is characterized, among other changes, by marked alterations in the cardiorespiratory system and the metabolic patterns during exercise. In highly trained athletes, insufficient training induces a rapid decline in VO2max, but it remains above control values. Exercise heart rate increases insufficiently to counterbalance the decreased stroke volume resulting from a rapid blood volume loss, and maximal cardiac output is thus reduced. Cardiac dimensions are also reduced, as well as ventilatory efficiency. Consequently, endurance performance is also markedly impaired. These changes are more moderate in recently trained subjects in the short-term, but recently acquired VO2max gains are completely lost after training stoppage periods longer than 4 wk. From a metabolic viewpoint, even short-term inactivity implies an increased reliance on carbohydrate metabolism during exercise, as shown by a higher exercise respiratory exchange ratio. This may result from a reduced insulin sensitivity and GLUT-4 transporter protein content, coupled with a lowered muscle lipoprotein lipase activity. These metabolic changes may take place within 10 d of training cessation. Resting muscle glycogen concentration returns to baseline within a few weeks without training, and trained athletes' lactate threshold is also lowered, but still remains above untrained values.